A newly recognized Mesozoic–Recent interspecific association: calcifying bacteria on decapod crustaceans. (12th March 2015) - Robin, Ninon; Petit, Gilles; Charbonnier, Sylvain
<x xml:space="preserve">Abstract</x> Using microscopy and spectroscopy tools, we succeeded in identifying undescribed diminutive epibionts (as epibiotic bacterial colonies) both on exceptionally well‐preserved fossil shrimps and on extant taxa (N. Robin, S. Bernard, J. Miot, M.‐M. Blanc‐Valleron, S. Charbonnier & G. Petit, submitted). This study outlines the ecological parameters of this totally newly recognized interspecific association. To this aim, the systematics and environmental setting of fossil and modern decapod hosts are described; count of bacterial colonies is made to assess prevalence and intensity; scanning electron microscopy is used to illustrate colonial growth patterns; and histological sections of the extant colonies nested in cuticle are stained to determine their incidence on the carapace of their decapod hosts. Thus, the prevalent and intense association is found on decapods of the superfamily Penaeoidea Rafinesque‐Schmaltz 1815 occupying up to 2 cm2 of the entire carapace. The association is here observed in deep environments such as that of the Jurassic La Voulte‐sur‐Rhône Lagerstätte. A non‐random distribution of colonial growth patterns is determined; it illustrates a favourite access site along the ventral margin of the shrimp carapace. SEM images and stained sections reveal strong colony embedment within the cuticle, but also damage such as erasing of the cuticular layers. This bioeroding effect, possibly linked to a feeding benefit to the bacteria, brings this interspecific association that has existed, for at least 160 myr, near to parasitism. In addition to illustrating a rare case of interaction in Recent forms that could be described due to previous recognition in fossils, it constitutes a textbook example of the preservation of intimate interactions through geological time.